Exploring Material Potentials for Product Design: In Pursuit of a Narrative-Based Approach - Alan, Ali Cankat; Gelmez, Koray; Efilti, Pelin; Yılmaz, Onur; Sezgin, Hande; Eniş, İpek Yalçın; Öztemur, Janset; Özdemir, Suzan (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This research proposes a narrative-based approach and two corresponding strategies as part of an interdisciplinary project. The approach could be an initial step in understanding the user’s first impression concerning materials experience and other material potentials, informing designers about translating them into product design decisions. The project combines Material-Driven Design (MDD) and user-centred research methods to develop composite Do-it-Yourself (DIY) materials by upcycling textile and plastic wastes. It aims to transform these materials into seven products designed for office environments that promote sustainability. The project’s design brief includes the product’s primary function, context, and target group. However, the MDD process follows the material exploration to decide on the product proposals formed towards the end. That calls for an alternative method that adapts MDD to broader product development scenarios, particularly those guided by a predefined design brief, to enhance the value of Materials Experience (MX) in conventional design processes. This research initially implements a design probe study to address this gap and to understand forty-six office worker participants’ first impressions of DIY material. Based on the study’s findings and initial material tinkering process within the research group, a need for a contextual elaboration of materials to address material potentials holistically, including experience, form, function, and affordance, became apparent. Hence, a narrative-based approach is grounded with materials agency in mind and strengthened with anthropomorphism and material journey mapping strategies to obtain insights for the abovementioned scenarios.